Dietary Starch Composition Effects on Cx43-intercellular Communication Channels and Short-Term Memory. (29th May 2020) - Francisco, Sarah; Smith, Kelsey; Rowan, Sheldon; Bargalló, Gemma Aragonès; Smith, Donald; Shukitt-Hale, Barbara; Taylor, Allen; Fernandez, Eloy Bejarano
Abstract: Objectives: Intercellular communication mediated by gap junctions is critical for cognitive and sensory functions and is disturbed with age and age-related diseases. We analyzed the impact of consuming a high glycemic diet or a low glycemic dietary intervention on Cx43, a component of gap junction intercellular communication channels associated with spatial short-term memory, in different age groups of mice. Methods: Male C57Bl6/J mice ( n  = 12–13) aged 7 months were fed equal amounts of either a high glycemic (HG) diet or a low glycemic (LG) diet for 1 month or 9 months. Within the 9-month feeding trial, half of the HG-fed animals were switched to the LG diet (HGxLG) at 4.5 months. The diets are isocaloric, but the HG starch is 100% composed of amylopectin, and the LG diet contains a 30% amylopectin/70% amylose mixture of starch and is digested much slower. We also analyzed tissues from a previous feeding trial where 12-month aged animals were fed these same diets over 12 months. The animals were weighed weekly, underwent intraperitoneal glucose tolerance tests to evaluate glycemic response, were tested for cognition using a novel object recognition test, and tissues were collected. Tissues including brain and eye samples were evaluated for Cx43, a component of gap junction intercellular communication channels, using immunohistochemistry and western blotting. Results: At both time points, compared to the LG-fed controls, the HG-fed animals had significantly increased (>10%) body weight, while the HGxLG crossover animals' body weight did not differ significantly from the LG-fed controls at 15 months. At 14 months, there was no significant difference in novel object recognition, although there was a trend of improved novel object recognition in the HGxLG crossover group. Cx43 gap junction protein accumulated in eye tissues of the HG-fed animals, and this accumulation was attenuated in the HGxLG group. Conclusions: These results suggest that detrimental consequences of a high glycemic diet during aging on cognitive function may be reversible, supporting that a switch in dietary habits may be an effective nutritional intervention in older adults. Funding Sources: USDA JM HNRCA Pilot Grant Program, NIH, USDA NIFA, USDA, Thome Memorial Foundation, and the BrightFocus Foundation.